2019
DOI: 10.1002/pola.29376
|View full text |Cite
|
Sign up to set email alerts
|

Gelating polypeptide matrices based on the difunctional N‐carboxyanhydride diaminopimelic acid cross‐linker

Abstract: This work reports the synthesis of a new difunctional N-carboxyanhydride (NCA) monomer, namely diaminopimelic acid (DAP), and its use in the one-pot preparation of an organogelating copolypeptide. The organogel is formed in situ through ring-opening polymerization (ROP) of DAP NCA from helical poly(ε-carbobenzyloxy-L-lysine) (PZLL) blocks in a mixture of dimethylformamide/chloroform. Gelation occurs by immobilizing the solvent through core crosslinking and is stabilized through physical intermolecular conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Several studies have been carried out using the ROP between 0°C and room temperature, where the ROP of NCA is usually initiated with a primary amine. For example, Murphy et al presented the ROP initiated with allylamine 135 . Sulistio et al presented the ROP for dendrimer synthesis.…”
Section: Scheme 17: Ring Opening Polymerization Of Ncas Initiated Witmentioning
confidence: 99%
“…Several studies have been carried out using the ROP between 0°C and room temperature, where the ROP of NCA is usually initiated with a primary amine. For example, Murphy et al presented the ROP initiated with allylamine 135 . Sulistio et al presented the ROP for dendrimer synthesis.…”
Section: Scheme 17: Ring Opening Polymerization Of Ncas Initiated Witmentioning
confidence: 99%
“…One solution to this issue would be through the use of amine-protecting groups, where deprotection (and concomitant liberation of the basic amine group) occurs under the conditions of filiform corrosion (i.e., pH ∼ 1.0–2.5). The tert -butylcarbamate (BOC) protecting group is widely used in the fine chemical and pharmaceutical industries as an acid-labile protecting group for amines but to the best of our knowledge has never been studied in coatings for pH-responsive corrosion prevention (Figure ). The use of this functional group may open opportunities to create multifunctional, pH-responsive polymers capable of both forming thermoset coatings and preventing propagation of FFC on aluminum substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular organogels have been attracting considerable attention over the last decades owing to their prospective and realized applications in numerous fields such as food, , cosmetics, drug delivery, encapsulation and controlled release of fragrance, and advanced materials. This kind of physical gel is generally formed by immobilizing organic solvents and oils in a three-dimensional network created by the entanglement of noncovalently self-assembled nanofibers. , Among many known gelators, peptidomimetic oligomers and polymers with secondary structures are particularly attractive gel-forming materials due to their intrinsic self-assembly propensity to hierarchically ordered architectures as well as the potential advantages like biocompatibility and bioactivity. , Previous studies have demonstrated that synthetic polypeptides or peptide-containing block copolymers exhibited good gelling activity in appropriate organic solvents in which a rigid α-helical or β-sheet motif plays a critical role in the formation of fibrillar networks. ,,, …”
Section: Introductionmentioning
confidence: 99%